Enhancing Pre Service Teachers TPACK through Reusable Learning Object-Based Blended Learning: A Comparative Study of Pre-Service Teachers with Diverse Self-Regulated Learning - Sudarman; Noor Ellyawati (Jurnal Pedagogi dan Pembelajaran, 2025)
The main issue is the lack of adequate resources and training for teachers, which affects the ability of curriculum developers to design effective strategies for both teachers and students. This study aims to examine the perspectives of curriculum developers on the obstacles encountered in the implementation of differentiated learning curriculum. The research uses a phenomenological method to explore information based on the direct experiences of curriculum developers. Data collection was conducted through in-depth interviews with 6 primary school teachers from the Penggerak School program. The collected data were analyzed using thematic analysis to identify key patterns emerging from their experiences. The results show that the integration of differentiated learning curriculum can be achieved through diagnostic assessment, teaching modules, or adjustments in teaching techniques by the teachers. The study also finds that differentiated learning is currently understood as a hidden curriculum, referring to elements not included in the official curriculum but still applied in teaching practices. Changes in the curriculum include simplification and more practical approaches, as well as a shift from a teacher-centered to a student-centered approach. The conclusion of this study highlights the importance of a comprehensive evaluation of differentiated learning implementation at all education levels to improve its effectiveness.